AESTHETIC ELEMENTS OF TURAK DANCE IN MUSI RAWAS DISTRICT: Elemen Estetis, TariSambut Turak - Puspa Sena, Puspa Sena; Rochayati, Rully; Kurniawan, Irfan (Universitas Negeri Surabaya, 2024)
This study is to determine the aesthetic elements of Tarisambut Turak in Musi Rawas Regency which includes motion, space, time. This research method will use qualitative method. Data collection techniques used by researchers are observation, interviews, and documentation. This research concludes that the aesthetic elements of Turak Peat Dance in Musi Rawas Regency consist of three parts, namely motion elements including movement and motion. The space element includes positive-negative space, floor pattern level, direction, dimension. Time elements include tempo, rhythm, and duration. The Turak Welcoming Dance movement was inspired by the Dutch colonization who wanted to control the area of the Lakitan Ulu Terawas Middle Tribe because the area was rich in natural resources, so it was developed in the form of a dance that could be enjoyed by the community through unique and meaningful movements that described the story of life during Dutch colonization. Turak Welcoming Dance has 5 varieties of movements, the arrangement of dance steps is sorted by researchers from the smallest to the largest. . Keywords: Aesthetic Elements, Turak Welcome Dance